2015
DOI: 10.3758/s13428-015-0564-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing perceptual change with an ambiguous figures task: Normative data for 40 standard picture sets

Abstract: In many research domains, researchers have employed gradually morphing pictures to study perception under ambiguity. Despite their inherent utility, only a limited number of stimulus sets are available, and those sets vary substantially in quality and perceptual complexity. Here we present normative data for 40 morphing picture series. In all sets, line drawings of pictures of common objects are morphed over 15 iterations into a completely different object. Objects are either morphed from an animate to an inan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
7
26
0
Order By: Relevance
“…One major assumption of our study is that the benefit for the gradual over the random presentation sequence is indicative of active exploration. While this benefit has also been reported elsewhere in the literature (see Egré et al 2018 for review), to our knowledge our study was the only one that showed this benefit in the context of morphing objects (Stöttinger et al 2016 ). In the original study, we used a between subjects design.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…One major assumption of our study is that the benefit for the gradual over the random presentation sequence is indicative of active exploration. While this benefit has also been reported elsewhere in the literature (see Egré et al 2018 for review), to our knowledge our study was the only one that showed this benefit in the context of morphing objects (Stöttinger et al 2016 ). In the original study, we used a between subjects design.…”
Section: Introductionsupporting
confidence: 83%
“…Prior to the patient study, we conducted an online study to determine the benefit of gradual presentations in a within subject design (Stöttinger et al 2016 ). The same picture sets used in the online study were then used in the patient study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult participants consistently report the target object at a point when the picture still represents more the first object than the second. Interestingly, this is only the case when the picture is presented in a gradual context compared to when the same picture is presented outside of the morphing context (Egré, Ripley, & Verheyen, 2018;Stöttinger et al 2018;Stöttinger, Sepahvand, Danckert, & Anderson, 2016). This effect is reversed after damage to the right hemisphere: right-brain-damaged patients need significantly more pictures to identify the emerging object when it is presented in the gradual compared to the individual condition (Stöttinger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%